Associations of Cumulative Family Risk With Academic Performance and Substance Involvement: Tests of Moderation by Child Reading Engagement. (24th August 2019) - Mason, W. Alex; Chmelka, Mary B.; Patwardhan, Irina; January, Stacy-Ann A.; Fleming, Charles B.; Savolainen, Jukka; Miettunen, Jouko; Järvelin, Marjo-Riitta
Abstract: Background : Exposure to cumulative contextual risk within the family early in life increases children's risk for substance involvement and related difficulties, including school failure, in adolescence and young adulthood. However, potential protective factors that buffer these risk associations are relatively untested, yet such tests are needed to improve existing preventive interventions for enhancing resilience among vulnerable children. Objectives : This study tested child reading engagement with parents at home as a moderator of cumulative family risk associations with adolescent substance use and academic performance as well as young adult substance abuse. Methods : Population register data as well as parent-report and adolescent-report data from 6, 963 participants of the 1986 Northern Finland Birth Cohort study were analyzed via structural equation modeling with latent variable interactions. Results : Results showed that child reading engagement moderated the associations of cumulative family risk with both adolescent academic performance and young adult substance abuse, but not with adolescent substance use. The highest levels of academic performance were observed under conditions of low risk and high reading engagement. Interestingly, cumulative family risk had a small positive association with substance abuse when reading engagement was low and a negative association with the young adult outcome when reading engagement was high. Conclusions/Importance : Moderation tests revealed complex interaction forms that may have implications for both theory and family-based preventive interventions.